Strategi Pengembangan Kader Dai Melalui Program Forum Dai & Ustadz Muda (FODIUM) Sumatera Utara - Hanirwan, Rizqi; Muniruddin (Kamaya: Jurnal Ilmu Agama, 2023)
This study aims to see how the FODIUM cadre strategy is capable of printing or creating competent Dai in North Sumatra. Researchers used qualitative research methods, data collection techniques were carried out through an interview process by understanding the formulation in depth, dynamically and meaningfully so that it would produce descriptive data in verbal words from what had been observed. The author observes North Sumatra FODIUM activities through social media and the internet then participates directly by visiting the location of the North Sumatra FODIUM secretariat on Jl. Kritura, Medan City to conduct direct interviews involving several informants at FODIUM. The results of this study indicate that there are several strategies carried out by the FODIUM organization in forming young Dai in North Sumatra, namely (1) Selection of Dai, (2) Coaching of Dai & (3) Placement of Dai in remote parts of North Sumatra. This strategy was formed in such a way with the hope of having a positive impact on the development of young Dai in North Sumatra.